Development and Application of an ELISA Assay Using Excretion/Secretion Proteins from Epimastigote Forms of T. cruzi (ESEA Antigens) for the Diagnosis of Chagas Disease. (25th September 2012) - Berrizbeitia, Mariolga; Figueroa, Milagros; Ward, Brian J.; Rodríguez, Jessicca; Jorquera, Alicia; Figuera, Maria A.; Romero, Leomerys; Ndao, Momar
Abstract : An indirect enzyme-linked immunoabsorbent assay (ELISA) for Trypanosoma cruzi was developed using epimastigote secretion/excretion proteins (ESEA antigens) obtained from axenic culture supernatants. A panel of 120 serum samples from subjects with confirmed Chagas disease ( n = 50 ), healthy controls ( n = 50 ), and patients with other parasitic diseases ( n = 20 ) was used to evaluate the new ESEA-based ELISA (ELISAESEA ). This new test had excellent sensitivity (98%) and acceptable specificity (88%). Cross-reactivity was observed largely in sera from subjects with Leishmania and Ascaris infections. Using Western blotting and epimastigotes from two distinct T. cruzi isolates, several polypeptide bands with molecular masses ranging from 50 to 220 kDa were detected in pooled chagasic sera. However, the band pattern for each isolate was different. These data suggest that an inexpensive and technically simple ELISA based on ESEA antigens is a promising new tool for the diagnosis of Chagas disease.